Synthesis and characterization of main chain thermotropic liquid crystalline polyesters based on methyl 4-[4 `-(omega-hydroxyalkoxy)blphenyl-4-yl]-4-oxobutyrate: Effects of keto group and connectivity on mesophasic characteristics of biphenyl based AB-typ - Ranganathan, T.; Ramesh, C. (Reactive & Functional Polymers, 2006)
A series of biphenyl based main chain thermotropic liquid crystalline polyesters, poly(hydroxyalkoxybiphenyl oxobutyrate) [PRBOB-2,n (n = 2-8)], containing various methylene spacers was synthesized by using the novel AB-type self-polycondensation route from the monomers, methyl 4-[4'-(omega-hydroxyalkoxy)biphenyl-4-yl]-4-oxobutyrate (HBOB-2,n). The mesophase characteristics of these polyesters was studied using DSC, polarized light optical microscopy and XRD techniques. The transition temperatures were found to decrease upon increasing the spacer length with an even polymer exhibiting higher transition temperature than the odd counterpart. The mesophase type also indicated an odd-even oscillation with the even members showing normal smectic phase and odd members exhibiting tilted smectic phase. The comparison of mesophasic characteristics of these polyesters with that of structurally similar AB-type polyesters indicated that the total number of atoms connecting the mesogen in a polymeric repeat unit governs the nature of the mesophase while the rigidity of the system dictates the magnitude of transition temperatures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AB approach; biphenyl mesogen; effect of connectivity; Liquid crystalline polyesters